2012
DOI: 10.5047/eps.2011.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The orientation of Titan’s dayside ionosphere and its effects on Titan’s plasma interaction

Abstract: A hybrid particle code has been used to examine how Titan's interaction with Saturn's magnetosphere is effected by the orientation of the dayside ionosphere with respect to the incident magnetospheric flow. The hybrid code self-consistently includes a version of Titan's ionosphere represented by 7 generic ion species, over 40 ionneutral chemical reactions, ion-neutral collisions and Hall and Pederson conductivities. Emphasis is placed on what effects the orientation angle has on the ion loss rates, ion densiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 67 publications
3
20
0
Order By: Relevance
“…Titan's chemically complex ionosphere is also quite dynamic and can be driven by magnetospheric pressure, thermal pressure, and thermospheric neutral winds [ Ledvina and Cravens, ; Cravens et al ., ; Bell et al ., ; Ma et al ., ]. A combination of forces can lead to transport of ionospheric parcels, and this can sometimes cause ionospheric densities, even on the dayside, to deviate from equilibrium state densities [ Cui et al ., ; Cravens et al ., ; Ledvina et al ., ]. Cui et al [] studied ion transport in Titan's ionosphere by using electron distribution data from nine close encounters of the Cassini spacecraft with Titan (TA‐T40) and comparing them with the diffusive equilibrium model results.…”
Section: Data‐model Comparisonsmentioning
confidence: 99%
“…Titan's chemically complex ionosphere is also quite dynamic and can be driven by magnetospheric pressure, thermal pressure, and thermospheric neutral winds [ Ledvina and Cravens, ; Cravens et al ., ; Bell et al ., ; Ma et al ., ]. A combination of forces can lead to transport of ionospheric parcels, and this can sometimes cause ionospheric densities, even on the dayside, to deviate from equilibrium state densities [ Cui et al ., ; Cravens et al ., ; Ledvina et al ., ]. Cui et al [] studied ion transport in Titan's ionosphere by using electron distribution data from nine close encounters of the Cassini spacecraft with Titan (TA‐T40) and comparing them with the diffusive equilibrium model results.…”
Section: Data‐model Comparisonsmentioning
confidence: 99%
“…[]. In situ magnetic field measurements [e.g., Neubauer et al ., ; Bertucci et al ., ] combined with post‐Cassini global MHD and hybrid models [ Ma et al ., ; Ledvina et al ., ] demonstrated that the magnetic field line topology is complex, particularly at lower altitudes. The magnetic fields produced by global models do not generally agree with magnetometer data below 1300 km or so [ Ulusen et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Several hybrid and MHD models have been produced to explain both observations of ionospheric plasma in Titan's more distant tail [cf. Keller and Cravens , 1994; Snowden et al , 2007; Modolo et al , 2007; Ma et al , 2007; Simon et al , 2007; Sillanpää et al , 2007; Lipatov et al , 2011; Ledvina et al , 2012] and the existence of fossil fields below Titan's exobase [cf. Ma et al , 2009; Simon et al , 2009].…”
Section: Introductionmentioning
confidence: 99%